Recombinant Human Epidermal Growth Factor/Quatsome Nanoconjugates: A Robust Topical Delivery System for Complex Wound Healing (Adv. Therap. 6/2021). Issue 6 (14th June 2021) - Ferrer‐Tasies, Lidia; Santana, Hector; Cabrera‐Puig, Ingrid; González‐Mira, Elisabet; Ballell‐Hosa, Lídia; Castellar‐Álvarez, Carla; Córdoba, Alba; Merlo‐Mas, Josep; Gerónimo, Haydee; Chinea, Glay; Falcón, Viviana; Moreno‐Calvo, Evelyn; et al.
Abstract : In article number 2000260, Jaume Veciana, Nora Ventosa and co‐workers report a soft, reliable, and scalable method based on compressed CO2 for obtaining nanoconjugates of recombinant human epidermal growth factors and nanovesicles. These nanoconjugates exhibit appropriate physicochemical properties together with an antimicrobial activity preventing infections that promote complete closure of complex wounds. Therefore, such nanoconjugates are a potential nanomedicine for the topical treatment of complex wounds, particularly diabetic foot ulcers.